Protective effects of arginine on fetal brain under maternal immobilization stress - E Enanat; H Delaviz; R Mahmoudi; A Roozbehi; M Jafari Barmak; پرستو راد; M Servatkhah; F Moreidikia (Armaghane Danesh Bimonthly Journal, 2015)
Background & aim: Arginine by regulating the biological activity of the brain plays an important role in reducing stress. Today's, stress is one of the century disease that created many problem.  This study conducted to determine the protective effect of arginine on nitric oxide levels in maternal fetal brain tissue under stress.